How does the Flow of Remittances Affect the Trade Balance of the Middle East and North Africa? - Mohammad Reza Farzanegan; Sherif Maher Hassan (Center for Economic Studies and ifo Institute (CESifo), 2016)
Middle Eastern and North African (MENA) economies have had the highest degree of dependency on received remittances worldwide over the last three decades. The region has also had the highest non-oil external trade balance deficit among developing countries. We examine the role of remittances in the trade balance of 11 labor-abundant MENA countries. Our panel regression analysis shows that the inflow of remittances has had an increasing effect on trade deficits by triggering import-led consumption expenditures. The results are robust after controlling for other drivers of trade deficit and fixed effects.
Keywords: D14; F22; F24; 330; remittances; Middle East and North Africa; trade balance; panel regression